Circular(2)-linear regression analysis with iteration order manipulation - Muhamad Irpan Nurhab; Badaruddin Nurhab; Tuti Purwaningsih; Ming Foey Teng (International Journal of Advances in Intelligent Informatics, 2017)
Data in the form of time cycle or point position to the angle of possibility is no longer suitable to be analyzed using classical linear statistic method because the direction and the angle influence the position between one data with other data. This paper aims to examine the comparison of Linear Regression Analysis with Circular Regression Analysis. The writing method used is literature review using simulation data. Data simulation and analysis is done with the help of R program. The results showed that circular data is better analyzed by Circular Regression Analysis rather than Classical Linear Regression Analysis. The use of classical linear statistic method is not recommended due to the direction and the angle influence the position between one data with other data.